2022
DOI: 10.3390/genes13071253
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Spectrum of Early-Onset Developmental and Epileptic Encephalopathies—Data from a Romanian Cohort

Abstract: Early-onset developmental epileptic encephalopathy (DEE) refers to an age-specific, diverse group of epilepsy syndromes with electroclinical anomalies that are associated with severe cognitive, behavioral, and developmental impairments. Genetic DEEs have heterogeneous etiologies. This study includes 36 Romanian patients referred to the Regional Centre for Medical Genetics Dolj for genetic testing between 2017 and 2020. The patients had been admitted to and clinically evaluated at Doctor Victor Gomoiu Children’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
2
3
0
Order By: Relevance
“…We report a significant proportion of variants (29%), both reported and novel, classified as VUSs in our study where the evidence is not as strong to classify these variants as pathogenic or benign. This was observed in previous studies 22,24 including individuals from underrepresented populations similar to our study 21,23 and represents a diagnostic challenge as these are not considered clinically diagnostic and require further clinical assessment, familial/segregation studies, RNA/splicing studies (for non-coding or splicing variants) or functional studies for further pathogenicity/ benignity reclassification, 22 which was not be possible in some families due to families declining familial/segregation studies, or unavailability of RNA/functional studies.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We report a significant proportion of variants (29%), both reported and novel, classified as VUSs in our study where the evidence is not as strong to classify these variants as pathogenic or benign. This was observed in previous studies 22,24 including individuals from underrepresented populations similar to our study 21,23 and represents a diagnostic challenge as these are not considered clinically diagnostic and require further clinical assessment, familial/segregation studies, RNA/splicing studies (for non-coding or splicing variants) or functional studies for further pathogenicity/ benignity reclassification, 22 which was not be possible in some families due to families declining familial/segregation studies, or unavailability of RNA/functional studies.…”
Section: Discussionsupporting
confidence: 93%
“…The estimated diagnostic yield of ES in DEEs in our study was 30%, which is similar to the previous reports for genome sequencing in DEEs (25%–45%) in recent studies 18–22 . There was marked genetic heterogeneity observed in our cohort, with variants identified in 33 genes and none of the genes being predominant in the cohort.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A smaller study of 36 patients with DEEs also reported that 64% of patients were experiencing GTCS. 48 One of the main goals of DEE treatment is to alleviate seizure burden by targeting the most problematic seizure type. 10 Although total cessation of seizures is not likely to be attainable for these patients, a reduction, especially of the most severe seizures, could mitigate neurodevelopmental delay, improve QOL, minimize polypharmacy, and reduce injury and premature death, namely, SUDEP.…”
Section: Discussionmentioning
confidence: 99%